Kajian Komprehensif Perkembangan Penelitian Nanoteknologi melalui Pendekatan Bibliometrik - Ni Putu Tiara Kusumadewi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Nanotechnology is a nanoscale technological innovation (1–1000 nm) that has been widely used in the pharmaceutical and medical fields, especially as a more effective and specific drug delivery system. This technology is able to increase the bioavailability of drugs, reduce side effects, and increase the efficacy of therapy. This study aims to explore the development and thematic focus of studies on nanotechnology published in PubMed during the period 2015–2025, using bibliometric methods and data visualization through the VOSviewer software. Data is collected through the Publish or Perish application with the keywords "nanotechnology", "analysis", and "data", and then visualized in the form of network visualization, overlay visualization, and density visualization to see the relationship between keywords and publication trends. The results of the analysis show that there are 198 relevant articles, with the most significant increase in the number of publications occurring in 2024. The visualization of the topic revealed four main clusters with dominant keywords such as nanotechnology, drug delivery, application, and cancer. In addition, research trends show a shift in focus from basic development towards clinical and therapeutic applications, which marks significant progress in the translation of basic science into health practice. The author's analysis shows that there are research groups that have significant contributions and close collaborations, especially from institutions and countries with high research capacity such as the United States, China, and India. This study provides a comprehensive overview of trends, directions, and patterns of collaboration in nanotechnology studies, and is expected to be a strategic reference for the development of research policies and scientific cooperation in the future, especially in the field of nanotechnology-based biomedicine and pharmaceuticals.